E-business tools adoption and export performance: Empirical evidence from Croatian companies - Mirna Leko Šimić; Antun Biloš; Josipa Mijoč (Journal of Entrepreneurship, Management and Innovation)
Technology development has enabled companies of all kinds, industries, and sizes to actively participate in international business. Information and communications technology (ICT), and especially e-business tools, are important for the international activities of companies. ICT empowers the company’s potential to contribute significantly to economic growth, as it plays a vital role in simplifying business processes and contributes to the improvement of the competitive market presence of a company. The objective of this research is to identify the level of e-business tools adoption in Croatian exporting companies and investigate its influence on their export performance. In the analysis of the level of e-business tools adoption, a partial OECD e-commerce maturity model was used, which measures several aspects of ICT readiness and intensity of web sites and e-commerce in exporting companies. Several distinct aspects of e-business tools adoption were examined, namely e-mail usage, internet usage in market research, promotion, e-commerce, and e-payment possibilities. The export performance level was measured through three elements: the export/total business activities ratio, the export/total revenue ratio and, additionally, the existence of multilingual official websites. Our findings provide enough evidence that e-business tools adoption has a positive correlation to export performance for Croatian exporters. However, it should be noted that three e-business tools adoption factors positively correlate with export performance: namely (1) e-mail use for correspondence with partners/suppliers/buyers, (2) use of the internet as a promotional tool for foreign markets and (3) e-payment use. Two remaining e-business tools adoption factors that were measured – (1) use of the internet as an information source on foreign markets/buyers/suppliers and (2) online ordering/sales, did not record a significant correlation with export performance. These findings imply that there is still room for better implementation of e-business tools in Croatian exporting companies, particularly regarding market research and online ordering and sales that can contribute to better export performance. With regard to international market geographical orientation, we found significant differences in exporting companies oriented toward geographically and culturally distant markets (non-regional and non-EU markets) that have a statistically higher level of e-business tools implementation in comparison to those exporting dominantly to regional and EU markets. This illustrates the significance of e-business tools adoption for reaching and managing those distant markets that are important for a number of Croatian exporters.